PENGARUH STRUKTUR MODAL YANG DIPROKSIKAN DENGAN DER, DAR, DAN LTDER TERHADAP EARNING PER SHARE (EPS) - Rotinsulu, Clara Neltje Meini (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to analyze the effect of capital structure, proxied by the Debt to Equity Ratio (DER), Debt to Asset Ratio (DAR), and Long Term Debt to Equity Ratio (LTDER), on Earnings Per Share (EPS) in companies listed on the Indonesia Stock Exchange (IDX). Capital structure is one of the important financial decisions that can affect a company's financial performance and the level of profits received by shareholders. EPS was chosen as the dependent variable because it reflects earnings per share, which is a primary concern for investors in making investment decisions. This study uses a quantitative approach with a causal associative method. The data used are secondary data in the form of annual financial reports of companies listed on the IDX during the study period. The sampling technique was carried out using purposive sampling, while the data analysis technique used multiple linear regression analysis preceded by descriptive statistical tests and classical assumption tests. The results of the study indicate that the Debt to Equity Ratio (DER), Debt to Asset Ratio (DAR), and Long-Term Debt to Equity Ratio (LTDER) each partially influence Earnings Per Share (EPS). This finding indicates that a company's capital structure policy, both in terms of total debt and long-term debt, plays a significant role in determining earnings per share. Therefore, optimal capital structure management is necessary for companies to improve financial performance and shareholder welfare.